2016
DOI: 10.1016/j.chroma.2016.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Purification of HIV-1 gag virus-like particles and separation of other extracellular particles

Abstract: Enveloped virus-like particles (VLPs) are increasingly used as vaccines and immunotherapeutics. Frequently, very time consuming density gradient centrifugation techniques are used for purification of VLPs. However, the progress towards optimized large-scale VLP production increased the demand for fast, cost efficient and scale able purification processes. We developed a chromatographic procedure for purification of HIV-1 gag VLPs produced in CHO cells. The clarified and filtered cell culture supernatant was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 39 publications
6
62
0
Order By: Relevance
“…This amount was equivalent to 1.4 × 10 12 or 2.1 × 10 12 HIV-1 gag VLPs per milliliter of monolith. This is within a similar range as reported for enveloped viruses and VLPs on monoliths [9,16]. Although the pressure limit was reached, it was possible to elute HIV-1 gag VLPs (Table 1) and a consistent process performance, compared to processes with a loading volume of 50 mL (Fig.…”
Section: Dynamic Binding Capacitysupporting
confidence: 85%
“…This amount was equivalent to 1.4 × 10 12 or 2.1 × 10 12 HIV-1 gag VLPs per milliliter of monolith. This is within a similar range as reported for enveloped viruses and VLPs on monoliths [9,16]. Although the pressure limit was reached, it was possible to elute HIV-1 gag VLPs (Table 1) and a consistent process performance, compared to processes with a loading volume of 50 mL (Fig.…”
Section: Dynamic Binding Capacitysupporting
confidence: 85%
“…Additionally, there are commercially available kits that advertise fast and easy EV isolation by precipitation (Momen-Heravi et al, 2013), although often leading to low purity and altered functionality of EVs (Van Deun et al, 2014; Gámez-Valero et al, 2016). Since purification of virus-like particles (VLPs) has come into focus for large-scale purification for potential therapeutic applications, and since EVs to some extent behave similar to VLPs (Steppert et al, 2016), it can also be imagined that these areas might be cross-talking for establishing the widely necessary and hoped-for standardized purification techniques. One method for the isolation of viruses makes use of polyethylene glycol (PEG) and can be adapted for purification of EVs.…”
Section: Isolation Of Extracellular Vesiclesmentioning
confidence: 99%
“…Currently exosomes are considered as potential new biopharmaceutical for treatment of several diseases and also for vaccination. It has also been shown that virus like particles and viruses may be contaminated with exosomes and other extracellular particles . Even they can be used for bioprocess monitoring, because the exosome content reflects the metabolic state of the cells .…”
mentioning
confidence: 99%